How would you rewrite the following equation into the Euler's (not improved) method?

y'= y -x - 1, y(0)

this is what I attempted:

Ysub(n+1) = Ysub (n)+ h (-x sub (n), Ysub (n) - 1)

Is this correct?

Printable View

- July 20th 2007, 08:39 AMgoogoogagaEuler's Method
How would you rewrite the following equation into the Euler's (not improved) method?

y'= y -x - 1, y(0)

this is what I attempted:

Ysub(n+1) = Ysub (n)+ h (-x sub (n), Ysub (n) - 1)

Is this correct? - July 20th 2007, 11:07 AMCaptainBlack